APLIKASI ABU BOILER DAN PUPUK NPK TERHADAP HASIL TANAMAN PAKCOY (Brassica rapa L.) - Sitepu, Erik Ananta; Hapsoh, Hapsoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
The research aimed to see the effect of ash of boiler, NPK fertilizer and get the best dosage to the result of pakcoy plant. The experiment was conducted in experimental station of Agriculture Faculty of Universitas Riau from April to May 2017. This research was conducted experimentally with Completely Randomized Design consisting with 2 factors and 3 replications. The first factor of dose of boiler ash wasÂ 400 g/m2, 600 g/m2,800 g/m2. The second factor of dose of NPK fertilizer was 20 g/ m2, 25 g/m2, 30 g/m2. Data have been statistically analyzed and examined further with Duncan Newâ€™s Multiple Range Test at the level of 5%. The results showed that the combination of ash of oil palm boiler and NPK fertilizer increased plant height, leaf number, leaf area, fresh weight of the plant and the weight of consumption of the plant. Boiler ash 600 g/m2 gave a better effect compared to giving 400 g/m2 and 800 g/m2. NPK 30 g/m2 fertilizer gave better effect compared to 20 g/m2 and 25 g/m2. Boiler ash 600 g/m2 and NPK 30 g/m2 fertilizer showed a better effect on leaf number parameter, leaf area, fresh weight and proper weight of plant pakcoy consumption. Weight worth consumption per plant pakcoy = 52.93 g.Keywords: Pakcoy plant, boiler ash, NPK fertilizer